Evaluating energy poverty and its effects using multi-dimensional based DEA-like mathematical composite indicator approach: Findings from Asia. (June 2022) - Lan, Jing; Khan, Sufyan Ullah; Sadiq, Muhammad; Chien, Fengsheng; Baloch, Zulfiqar Ali
Abstract: The objective of the study is to develop a multidimensional energy poverty index (EPI). The current study examines the impacts of multidimensional energy poverty indicators using mathematical composite index and, econometric models for five Asian countries. Multidimensional energy poverty indicator is used to evaluate the overall consequences of these region's energy poverty. It is estimated that EPI of Nepal region is 0.02, Sri Lanka composite score (CS) is 0.03, and Bangladesh's CS is 0.011, which are the maximum affected nations. In contrast, India's CS is above 0.88 and Pakistan's CS is above 0.49 and are expected to be the minimum energy poor. Of the total energy production, 79% is based on traditional fuels, followed by 12% based on petroleum products. Results further highlight the availability of electricity, the time it earns to obtain electricity, access to clean energy, and cooking technology have substantial positive relationship with region's EPI. Private investment in energy sector is a consistent negative component in EPI. In other economies, poverty headcount ratio coefficients are notably positive. Implemented energy policies and their impact on access to energy in South Asian region, highlight possible challenges but also benefits of the association between energy poverty and access to energy. Highlights: Multifunctional energy poverty indicator is used to evaluate overall consequences. The composite scores of Nepal, Sri Lanka and Bangladesh are 0.02, 0.03 is 0.011. India and Pakistan are the minimum expected to be energy poor. Private investment in the energy sector is a consistent negative component in EPI. The poverty headcount ratio coefficients are notably positive.